2021
DOI: 10.1002/jcph.1956
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 1 Trial to Evaluate the Relationship Between Fluoride Intake and Urinary Fluoride Excretion in Healthy Participants

Abstract: Chronic overexposure to fluoride can have deleterious effects in the musculoskeletal system. Some fluorine‐containing therapeutics, such as voriconazole, release fluoride through metabolism. Therefore, drug‐related fluoride exposure should be assessed for novel therapeutics suspected of releasing fluoride through metabolism. Two trials were conducted to identify the optimal method of assessing drug‐related fluoride exposure. In trial 1, designed to assess reproducibility of fluoride pharmacokinetics in urine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…These findings are consistent with a corresponding trial that indicated that urine sampling offers a more consistent and accurate method of assessing fluoride exposure in participants administered a fluoride‐restricted diet relative to plasma measurement. 9 Data from the current trial demonstrated readily detectable fluoride levels in urine samples, which increased in a dose‐dependent manner.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…These findings are consistent with a corresponding trial that indicated that urine sampling offers a more consistent and accurate method of assessing fluoride exposure in participants administered a fluoride‐restricted diet relative to plasma measurement. 9 Data from the current trial demonstrated readily detectable fluoride levels in urine samples, which increased in a dose‐dependent manner.…”
Section: Discussionmentioning
confidence: 68%
“…To decrease variability due to dietary fluoride intake, the trial incorporated a fluoride restricted diet run‐in phase of 5 days, which was determined to be sufficient based on previously collected data. 9 However, urine fluoride excretion continued to decline slightly in some participants receiving placebo in period 2 (Table S1 ), indicating the value of comparing outcomes with a within‐group baseline and a parallel group receiving placebo in this trial. Fluorosis is not known to be an adverse event that is commonly observed in PLWH, but the risk of bone‐related adverse events needs to be considered when investigating new antiretroviral therapies.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations